2003
DOI: 10.1021/ie0209428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chlorine on the Properties of Ru/Al2O3

Abstract: Ru/Al 2 O 3 catalysts with different chlorine contents were prepared using RuCl 3 as the precursor. Different HCl concentrations in the impregnation solution or different treatments after impregnation were used. The catalysts were characterized by temperature-programmed reduction, X-ray photoelectron spectroscopy, and hydrogen chemisorption. They were tested in the selective hydrogenation of benzene to cyclohexene in a stirred tank reactor at 373 K and 3 MPa hydrogen pressure. It was found that different elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 13 publications
8
65
0
5
Order By: Relevance
“…(2) Considering the Pauling electronegativities of Ru (2.2), N (3.0) and O (3.4), metallic Ru may donate an electron to O in the ether linkages (or N in the amine groups) and a lot of Ru δ+ species may be formed. Mazzieri et al 30 found that the cyclohexene selectivity increased with the decrease of the Ru 0 /Ru δ+ ratio. They suggested that cyclohexene might be more weakly adsorbed on the most electron-deficient Ru species and easily desorbed by avoiding its further hydrogenation to cyclohexane and the cyclohexene selectivity increased.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Considering the Pauling electronegativities of Ru (2.2), N (3.0) and O (3.4), metallic Ru may donate an electron to O in the ether linkages (or N in the amine groups) and a lot of Ru δ+ species may be formed. Mazzieri et al 30 found that the cyclohexene selectivity increased with the decrease of the Ru 0 /Ru δ+ ratio. They suggested that cyclohexene might be more weakly adsorbed on the most electron-deficient Ru species and easily desorbed by avoiding its further hydrogenation to cyclohexane and the cyclohexene selectivity increased.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the preparation of cyclohexene has attracted great research interest academically and industrially. Among various synthetic routes, such as cyclohexanol dehydration, cyclohexane halide dehydrohalogenation, cyclohexane dehydrogenation and so on [1][2][3], selective hydrogenation of benzene to cyclohexene (SHBC) receives much attentions due to economical requirements and environmental considerations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…4(d)-(f) showed one hydrogen reduction peak centered near 520 K assigned to the reduction of RuO2 to Ru 0 . No ruthenium chloride or ruthenium oxychloride were observed over the catalysts 43), 44) . However, ruthenium oxychloride was clearly observed on Ru/ Mn(Cl)/Al2O3 in Fig.…”
Section: Resultsmentioning
confidence: 97%